Increased Pulse Pressure Variability Within the First 24 Hours Leads to Poor Disposition in Subarachnoid Hemorrhage Patients. (4th February 2021) - Dowlati, Ehsan; Triano, Matthew J; Felbaum, Daniel R; Mai, Jeffrey C; Aulisi, Edward F; Armonda, Rocco A; Chang, Jason J
Abstract: Background: Aneurysmal subarachnoid hemorrhage (SAH) continues to be associated with significant morbidity and mortality despite treatment advancements. Although high blood pressure (BP) remains a significant risk factor in aneurysmal SAH and rerupture, the role of BP parameters and fluctuation in prognostication remains unclear. We sought to define how BP parameters and variability within 24 hours of hospitalization in acute-onset SAH affects patient discharge outcomes. METHODS: We retrospectively analyzed a prospectively collected cohort of SAH patients. Hourly BP parameters, including systolic BP (SBP), diastolic BP, pulse pressure (PP), and their corresponding variability (delineated by SD), were collected to investigate associations with the primary endpoint of discharge disposition. RESULTS: One hundred and seventy-four SAH patients were included in the study. On bivariate analysis, Hunt–Hess (HH) score, Fisher grade, intraventricular hemorrhage, external ventricular drain placement, and SBP and PP variability were significantly associated with a poor disposition. Poor disposition was significantly associated with age, HH score, intraventricular hemorrhage, and PP variability on multivariate analysis. PP variability remained an independent predictor for poor disposition (odds ratio 1.11, 95% confidence interval, 1.02–1.21, P = 0.02) when adjusting for potential confounders. Conclusions: Increased BP and PP variability within the first 24 hours of admission portends a poor discharge disposition for aneurysmal SAH patients. Graphical Abstract: